Destroying the wall : in search of "unity in difference" in 'Onjeong' biblical hermeneutics on the basis of Korean and South African political and cultural contexts - Kim, Hyangmo (Department of Religious Studies, 2014)
Includes bibliographical references ( p. 212-234).